2022
DOI: 10.3847/1538-4357/ac7872
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Observational Signatures of Cloud–Cloud Collision and Hub-filament Systems in W31

Abstract: To understand the formation process of massive stars, we present a multiscale and multiwavelength study of the W31 complex hosting two extended H ii regions (i.e., G10.30-0.15 (hereafter, W31-N) and G10.15-0.34 (hereafter, W31-S)) powered by a cluster of O-type stars. Several Class i protostars and a total of 49 ATLASGAL 870 μm dust clumps (at d = 3.55 kpc) are found toward the H ii regions where some of the clumps are associated with the molecular outflow activity. These results confirm the existence of a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…While these 'bridging features' are frequently identified in other regions (e.g. Maity et al 2022 ), their identification is somewhat subjectiv e, and man y claimed detections bear very little resemblance to the Haworth et al ( 2015 ) diagnostic. The relatively uniform increase in HCN and other line intensities with column density in three out of four clouds suggests that these collisions may be less common than is often assumed.…”
Section: Cloud Collisionsmentioning
confidence: 95%
“…While these 'bridging features' are frequently identified in other regions (e.g. Maity et al 2022 ), their identification is somewhat subjectiv e, and man y claimed detections bear very little resemblance to the Haworth et al ( 2015 ) diagnostic. The relatively uniform increase in HCN and other line intensities with column density in three out of four clouds suggests that these collisions may be less common than is often assumed.…”
Section: Cloud Collisionsmentioning
confidence: 95%
“…As disturbances from gas collisions are added to developed clouds, amplified magnetic fields significantly enhance the effective Jeans mass and then promote the formation of dense hub filaments in a short time of order 0.1 Myr after the shock compression (Inoue et al 2018). It is also worth noting that some studies, which have meticulously examined the large-scale gas motions of molecular clouds, have shown that hub filaments are embedded in the regions where interaction between two clouds is ongoing (e.g., Dewangan 2022; Maity et al 2022Maity et al , 2023. The precolliding system possibly corresponds to Stage I (Kumar et al 2020), which comprises more than two systems with individual, simple filamentary clouds in the hub-filament cluster formation evolutionary sequence.…”
Section: Hub-filament Development At the Latest Phase Of The Gmc Life...mentioning
confidence: 99%
“…While these 'bridging features' are frequently identified in other regions (e.g. Maity et al 2022), their identification is somewhat subjective, and many claimed detections bear very little resemblance to the Haworth et al (2015) diagnostic. The relatively uniform increase in HCN and other line intensities with column density in three out of four clouds suggests that these collisions may be less common than is often assumed.…”
Section: Cloud Collisionsmentioning
confidence: 99%